Mainstreaming Nature-Based Solutions for Climate Adaptation in Southeast Asia: A Systematic Review - Tun K.Z.; Pramanik M.; Chakrabortty R.; Chowdhury K.; Halder B.; Pande C.B.; Mukhopadhyay A.; Zhran M. (Springer Science and Business Media Deutschland GmbH, 2025)
Southeast Asia undergoes varying degrees of urbanisation, with some nations at advanced stages and others in developing phases. Nature-based Solutions (NbS) are crucial for boosting urban resilience, but comprehending how to implement them effectively in urban environments is an ongoing process. This study seeks to comprehensively explore the current knowledge on urban resilience and ecosystem services through NbS in Southeast Asia (SEA). Only empirical studies conducted on nature-based solutions and recommendations were included in this review, considering keywords such as, ?ecosystem services?, ?nature-based solutions?, ?urban? and ?Southeast Asia? in various combinations. A total of 102 papers, from 62 different sources, were selected to analyse in this study. The study of nature-based solutions for enhancing urban resilience in Southeast Asia reflects a growing interest and heightened awareness of this climatic phenomenon. This trend is notably demonstrated by a significant increase in published articles since 2014. The study indicates the current state of NbS research in Southeast Asia, emphasising the importance of ongoing interdisciplinary collaboration, international engagement, and a dedicated focus on sustainable urban development and green infrastructure to effectively tackle challenges posed by the urban heat island phenomenon in the region. Graphical abstracts: (Figure presented.) ? King Abdulaziz University and Springer Nature Switzerland AG 2024.